The Challenge of Visibility and Evaluation in the Humanities and Social Sciences - Žic Fuchs, Milena (Array, 2013)
The paper discusses two interlinked issues: how to enhance visibility of research outputs in the Humanities and the Social Sciences, and how to set up evaluation systems for the Humanities and Social Sciences, systems that would reflect the specific nature of their research outputs. Special attention is paid how to deal with national languages and monographs as the mainstay of especially Humanities research. The difference between bibliometric and bibliographic databases is discussed.